PERAN ESG DALAM MENGEMBANGKAN BAHAN AJAR PENDIDIKAN ISLAM YANG RESPONSIF TERHADAP ISU GLOBAL - Nurcahyati Sinulingga, Neng; Prandana, Tomi; Awaliyah, Zahrani; Rangkuti, Abrilliyansyah Abni; Annisa, Sapna (Universitas Medan Area, 2024)
The integration of Environmental, Social, and Governance (ESG) values in Islamic education is a strategic step to form a generation that is responsive to global challenges. This study aims to analyze the relevance of ESG values in Islamic education, identify implementation challenges, and formulate strategies to integrate these values into teaching materials. The research method uses a qualitative approach with a literature review. The results of the study show that ESG is relevant to maqashid sharia principles that include environmental sustainability, social justice, and ethical governance. However, the main challenges include educators' lack of understanding, limited resources, cultural resistance, and inadequate pedagogical approaches. Suggested strategies include developing a maqashid sharia-based curriculum, intensive training for educators, project-based learning approaches, and collaboration with international organizations to support ESG implementation. With this approach, Islamic education can be a means to form a generation that is religious, socially responsible, and aware of environmental sustainability, making a real contribution in facing global challenges. Keywords: ESG, Islamic Education, Maqashid Syariah, Global Challenges. Keywords: Environmental; Social; Governance; Islamic Education